Knowledge about iron rich foods and its consumption pattern among adolescent girls in an urban slum of Kolar - K., Latha; D., Mohan H. (International Journal Of Community Medicine And Public Health, 2017)
Background: Adolescent anemia is a long standing public health problem in India. According to NFHS-3 almost 56% of adolescent girls aged 15-19 years suffer from some form of anaemia. This study was conducted to assess the knowledge and consumption practices of iron rich foods and also to estimate the haemoglobin levels among adolescent girls in urban slum of Kolar. Methods: Around 170 adolescent girls in the age group of 10-19 years in Gandhinagar area of Kolar town were included and administered the interview questionnaire. They were invited to Anganwadi centres on a fixed day for estimation of haemoglobin. 92 girls attended the screening and were given awareness by distributing hand out. Results: The mean age of the girls was 15.06±2.230. The mean age at menarche was 13.38±1.158. Majority of girls 58.8% were in 15-19 year age group, 94.1% were aware about iron rich foods and 66.5% were aware of weekly iron and folic acid supplementation (WIFS). Around 92 (54.1%) girls were screened for haemoglobin levels and 32 (34.8%) were found to have anaemia. The factors associated with anaemia among adolescent girls included attaining menarche and no toilet usage which was statistically significant (p value <0.05). Conclusions: The supplementation of iron and folic acid tablets alone is not sufficient and it has to be effectively combined with improving the awareness about iron rich foods and its consumption practices to reduce the prevalence of anaemia.